Her smell [videorecording (DVD)] - Perry, Alex Ross; Perry, Alex Ross; Perry, Alex Ross; Moss, Elisabeth, 1982-; Moss, Elisabeth, 1982-; Delevingne, Cara, 1992-; Stevens, Dan, 1982- (Gunpowder & Sky, 2019)
A punk rock star struggles with addiction while trying to regain success.